Sewage sludge in the revegetation of degraded area - Bezerra, Flávio Barbosa; Oliveira, Maria Alice Cruz Lopes de; Perez, Daniel Vidal; Andrade, Aluísio Granato de; Meneguelli, Neli do Amaral (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to verify the viability of using the sludge produced by Estação de Tratamento de Esgoto do Aeroporto Internacional do Rio de Janeiro (Etar-Apoio), in the revegetation process of a degraded area located in this airport. The addition of such material to the soil increased significantly the organic matter contents, nitrogen, phosphorus, magnesium, potassium and calcium, as well as the cation exchange capacity (pH 7). The micronutrients Fe, Zn, and Cu increased with the sewage sludge application. However, this behavior is not related to the soil pH decrease, but to the CEC increment and to the organic matter increase. No significant sewage sludge effect was observed in the development of the species used (Mimosa caesalpiniifolia – Sabiá – and M. bimucronata – Maricá). However, it was observed a significant interaction between the rates of sewage sludge application and the plants. Those results have indicated that the revegetation process used was a feasible alternative to the final disposal of the sewage sludge.